Numerical study on a new adjustable multi-hole throttling device for natural gas flooding - Xing, Xuesong; Chen, Huan; Ma, Yingwen; Yu, Jifei; Xue, Dedong; Zou, Minghua; Kou, Lei (Frontiers in Chemical Engineering, 2024)
Natural gas flooding represents a significant technique for the enhancement of oil recovery, thereby facilitating the efficient utilization of oil and gas resources. In the injection and production system, the throttling gas nozzle is a key component that adjust the injection pressure according to the reservoir's pressure. However, current throttling gas nozzles utilize a fixed structure, which presents a challenge in achieving online control of flow rate and pressure drop. Therefore, a new adjustable multi-hole throttling device was proposed in this paper, allowing for the regulation of pressure loss by changing the number of flowing holes. In order to gain insight into the operational principles and pressure drop characteristics of this new throttling device, the SST k-ω turbulence model and the NIST physical property model were employed to simulate the supercritical natural gas flow in the nozzle. The results demonstrate that there is an uneven distribution of velocity between the channels of the downhole multi-hole throttling device. The velocity in a single nozzle channel exhibits a trend of initially increasing rapidly and then decreasing, while the pressure exhibits an initial decrease, which is then followed by a slight increase. The pressure drops of the nozzle under different flow rates and flowing hole numbers were acquired, revealing that the pressure drop of the multi-hole throttling device is inversely proportional to the number of holes. The adjustment accuracy of pressure drop and flow rate is higher when the number of holes is between 4 and 6. However, a significant increase in pressure drop occurs when the number of holes is less than 3, resulting in poorer regulation accuracy. Furthermore, a pressure drop prediction model was developed based on the numerical results, which provides guidance for the application and design of the throttling device.